Corticosterone Treatment and Incubation Time After Contextual Fear Conditioning Synergistically Induce Fear Memory Generalization in Neuropeptide S Receptor-Deficient Mice - Kolodziejczyk, Malgorzata H.; Fendt, Markus (Frontiers in Neuroscience, 2020)
Fear memory generalization is a learning mechanism that promotes flexible fear responses to novel situations. While fear generalization has adaptive value, overgeneralization of fear memory is a characteristic feature of the pathology of anxiety disorders. The neuropeptide S (NPS) receptor (NPSR) has been shown to be associated with anxiety disorders and has recently been identified as a promising target for treating anxiety disorders. Moreover, stress hormones play a role in regulating both physiological and pathological fear memories and might therefore also be involved in anxiety disorders. However, little is known about the interplay between stress hormone and the NPS system in the development of overgeneralized fear. Here, we hypothesize that NPSR-deficient mice with high corticosterone (CORT) levels during the fear memories consolidation are more prone to develop generalized fear. To address this hypothesis, NPSR-deficient mice were submitted to a contextual fear conditioning procedure. Immediately after conditioning, mice received CORT injections (2.5 or 5 mg/kg). One day and 1 month later, the mice were tested for the specificity and strength of their fear memory, their anxiety level, and their startle response. Moreover, CORT blood levels were monitored throughout the experiment. Using this protocol, a specific contextual fear memory was observed in all experimental groups, despite the 5-mg/kg CORT-treated NPSR-deficient mice. This group of mice showed a generalization of contextual fear memory and a decreased startle response, and the females of this group had significantly less body weight gain. These findings indicate that interplay between CORT and the NPS system during the consolidation of fear memories is critical for the generalization of contextual fear.